2020
DOI: 10.3389/fgene.2020.00193
|View full text |Cite
|
Sign up to set email alerts
|

circGNB1 Facilitates Triple-Negative Breast Cancer Progression by Regulating miR-141-5p-IGF1R Axis

Abstract: As an intriguing class of RNA, circular RNAs (circRNAs) are vital mediators of various diseases including cancers. However, the biological role and underlying mechanism of the majority of circRNAs are still ambiguous in the progression of triple-negative breast cancer (TNBC). In this study, we characterized and further investigated hsa_circ_0009362 (circGNB1) by reanalyzing the circRNA microarray profiling in our previous study. Validating by qRT-PCR, circGNB1 was overexpressed in TNBC cell lines and high expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 39 publications
1
42
1
Order By: Relevance
“…The worse OS associated with miR-141 and miR-181 can be explained by their suggested oncogenic role. Conversely, our results are completely at odds with Ping et al, who demonstrated that high expression of miR-141 was associated with better OS in TNBC patients [ 67 ]. One intrinsic limitation of our study is the small sample size, which did not allow us to study the associations between the three studied miRNAs and the clinical characteristics of the patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The worse OS associated with miR-141 and miR-181 can be explained by their suggested oncogenic role. Conversely, our results are completely at odds with Ping et al, who demonstrated that high expression of miR-141 was associated with better OS in TNBC patients [ 67 ]. One intrinsic limitation of our study is the small sample size, which did not allow us to study the associations between the three studied miRNAs and the clinical characteristics of the patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, circRASSF2 regulates laryngeal squamous-cell carcinoma cells malignancy by sponging miR-302b-3p and enhancing the expression of IGF1R [ 101 ]. Similarly, circGNB1 sponges miR-141-5p and facilitates triple-negative breast cancer progression by upregulating the IGF1R [ 102 ]. A circRNA derived from backsplicing of the IGF1R itself, named circIGF1R, is detectable in hepatocellular carcinoma clinical specimens and promotes cell proliferation by activating the PI3K/Akt pathway [ 103 ].…”
Section: Novel Regulators Of the Igf System And Their Impact In Camentioning
confidence: 99%
“…Likewise, circKIF4A and circITCH were proved to upregulate its parental genes via acting as sponges for miRNAs thereby mediating TNBC progress [ 51 , 52 ]. Additionally, more miRNA-sponge functions of circRNAs have been and are being validated in TNBC, including circUBAP2/miR-661/MTA1 [ 53 ], circPLK1/miR-296-5p/PLK1 [ 54 ], circTFCP2L1/miR-7/PAK1 [ 55 ], circAHNAK1/miR-421/RASA1 [ 56 ], circAGFG1/miR-195-5p/CCNE1 [ 57 ], circZEB1/miR-448/eEF2K [ 58 ], circGNB1/miR-141-5p/IGF1R [ 59 ], circRPPH1/miR-556-5p/YAP1 [ 60 ], circCDYL/miR-190a-3p/TP53INP1 [ 61 ], circEIF3M/miR-33a/cyclinD1 [ 62 ], circUBE2D2/miR-512-3p/CDCA3 [ 63 ], and circPGAP3/miR-330-3p/Myc [ 64 ].…”
Section: Regulatory Mechanisms Of Circrnas In Tnbcmentioning
confidence: 99%
“…Majority circRNAs identified in TNBC are characterized by oncogenic features. Specifically, circRPPH1 , circSEPT9 , circGNB1 , circPGAP3 , circUBE2D2 , circRAD18 , circAGFG1 , circKIF4A , circPLK1 , circUBAP2 , circEPSTI1 , and circGFRA1 were upregulated in both TNBC cells and tissues, and high expression of these circRNAs was able to promote tumor cell proliferation both in vitro and in vivo, and was associated with larger tumor sizes and shorter survival times for TNBC patients [ 29 , 46 , 49 , 51 , 53 , 54 , 57 , 59 , 60 , 63 , 64 , 78 ]. Similarly, circZEB1 , circEIF3M , circHER2 , hsa_circ_0131242 , hsa_circ_0005320 , hsa_circ_069718 , hsa_circ_0058514 , and circTFCP2L1 were overexpressed in TNBC cells and tissues, and they appeared to promote cell proliferation and tumor growth of TNBC [ 55 , 58 , 62 , 75 , 79 – 82 ].…”
Section: Role Of Circrnas On the Biological Functions Of Tnbcmentioning
confidence: 99%
See 1 more Smart Citation